Prevention of viral infection transmission in dental practice - Jovana Hrisa-Samardžija; Marina Milinković; Biljana Mijović (Биомедицинска истраживања, 2019)
Hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) are the main bloodborne pathogens and are of considerable interest for the dental team. In dentist's surgery, HBV, HCV and HIV infections can be transmitted via direct contact with blood and saliva containing blood, or via indirect contact with contaminated dental instruments during and after work. The use of sharp dental instruments at work, as well as the treatment of patients who feel pain and are under stress, present risk factors for exposure incident development. For this reason, special measures to protect against viral infections should be imposed. A vaccine presents specific protection against HBV. Non-specific protection includes the protection of staff and patients, specific approach while working with contaminated dental instruments, specific hygiene of working surfaces and equipment in the dentist's surgery, as well as medical waste disposal. Prevention of exposure is the primary strategy leading to the reduction in occupational infections. In addition to this, for HBV, HCV and HIV infections a post-exposure prophylaxis is prescribed, the application of which has a satisfactory efficiency.
Keywords: hepatitis B virus; hepatitis C virus; human immunodeficiency virus; dental service; specific and non-specific protective measures